Organizational Culture and Its Impact on Marketing Strategies for Business Success: Insights from Bank Tabungan Negara, Makassar - Riu, Isma Azis (PT Maju Malaqbi Makkarana, 2024)
Organizational culture refers to the values, norms, beliefs, and behaviors that exist within an organization. It reflects the organization's unique identity and characteristics, and influences the way people interact and work within it. Organizational culture can shape the work atmosphere, employee motivation, and overall organizational performance. Organizational culture can have an impact on many things, such as employee morale, productivity, work quality, employee loyalty, and the organization's ability to adapt to change. Organizations must build and maintain a culture that aligns with their values and goals and creates a positive and supportive environment for their members. Therefore, organizational culture is a characteristic that distinguishes other companies. The research conducted aims to determine the role of organizational culture in marketing strategy in achieving the success of the Makassar City State Savings Bank company. This study uses a qualitative method by collecting data through interviews with one of the employees of the State Savings Bank. The role of organizational culture in marketing strategy in achieving the success of the Makassar City State Savings Bank in several ways, namely customer orientation, innovation, team collaboration, open communication and Corporate Values and Identity.